PENGARUH EMOJI DALAM MENGGANTIKAN FUNGSI GRAMATIKAL EKSPRESI TERHADAP PENGGUNAAN BAHASA INDONESIA DALAM KOMUNIKASI DI DUNIA DIGITAL - Parulian Sibuea; Ratu Sabrina Adfi Nasution; Gian Safitri; Witria Rahmani Zahara; Suhaila Aprilia (STKIP Subang, 2025)
The increasing use of emojis in digital communication, particularly on social media, is influencing how users express meaning in Indonesian. This study aims to analyze the impact of emojis as a substitute for grammatical expressions on the use of Indonesian in digital communication.This study used a quantitative approach with a questionnaire as the data collection technique. The results showed that emojis are often used as substitutes for certain grammatical elements, such as emotional expression, emphasis, and intonation in written communication. The use of emojis is considered to clarify the message, but in certain contexts, it has the potential to diminish the use of standard Indonesian language structures.Thus, the use of emojis has a dual impact: as a communication tool and as a factor influencing changes in language patterns in the digital space. Based on questionnaire data,(87.4%)103 of people use emojis to convey expressions in digital communication. Their use risks eroding the ability to speak correct Indonesian.To prevent this, we've found that implementing the 4M 1J concept (Separating the person you're speaking to, Cultivating complete sentences, Adding emojis as complements, Practicing expressing feelings, and Don't delete important words) is essential. This ensures that emoji use continues to function as a support for digital communication without degrading the rules of good and correct Indonesian.